2014
DOI: 10.1371/journal.pone.0108233
|View full text |Cite
|
Sign up to set email alerts
|

Different Expression Patterns of Genes from the Exo-Xis Region of Bacteriophage λ and Shiga Toxin-Converting Bacteriophage Ф24B following Infection or Prophage Induction in Escherichia coli

Abstract: Lambdoid bacteriophages serve as useful models in microbiological and molecular studies on basic biological process. Moreover, this family of viruses plays an important role in pathogenesis of enterohemorrhagic Escherichia coli (EHEC) strains, as they are carriers of genes coding for Shiga toxins. Efficient expression of these genes requires lambdoid prophage induction and multiplication of the phage genome. Therefore, understanding the mechanisms regulating these processes appears essential for both basic kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(67 citation statements)
references
References 45 publications
1
66
0
Order By: Relevance
“…Previous studies indicated that either overexpression or deletion of the whole exo-xis region or particular genes and ORFs affect the lytic cycle of lambdoid bacteriophages after infection of E. coli bacteria under standard laboratory conditions (Łoś et al, 2008a;Bloch et al, 2013 andBloch et al, 2014;Licznerska et al, 2016b;Dydecka et al, 2017 andDydecka et al, 2018). Here, we demonstrate that in one-step growth experiment both lambdoid bacteriophages with the deletion of orf73 present shorter latent period and more efficient intracellular lytic development relative to the wild-type viruses (Fig.…”
Section: Deletion Of Orf73 Influences Phage Infection and Host Survivalsupporting
confidence: 53%
See 3 more Smart Citations
“…Previous studies indicated that either overexpression or deletion of the whole exo-xis region or particular genes and ORFs affect the lytic cycle of lambdoid bacteriophages after infection of E. coli bacteria under standard laboratory conditions (Łoś et al, 2008a;Bloch et al, 2013 andBloch et al, 2014;Licznerska et al, 2016b;Dydecka et al, 2017 andDydecka et al, 2018). Here, we demonstrate that in one-step growth experiment both lambdoid bacteriophages with the deletion of orf73 present shorter latent period and more efficient intracellular lytic development relative to the wild-type viruses (Fig.…”
Section: Deletion Of Orf73 Influences Phage Infection and Host Survivalsupporting
confidence: 53%
“…According to available data, this ORF remains under control of the early p L and BPROM-predicted p 1 promoters (Fig. 1) (Bloch et al, 2014). As we demonstrated in Table 2, the nucleotide sequence of orf73 is highly conserved among the group of lambdoid viruses, with the scores of similarities ≥97%.…”
Section: The Nucleotide Sequences Of Orf73 and Amino Acid Sequences Omentioning
confidence: 63%
See 2 more Smart Citations
“…Gene expression was determined by RT-qPCR essentially as described previously (Bloch et al, 2014). All experiments were performed with the LightCycler 480 Real-Time PCR System (Roche), using cDNA samples from lysogenic bacteria.…”
Section: Methodsmentioning
confidence: 99%